2008
DOI: 10.1007/s12031-008-9120-4
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Oxygen Restriction Does Not Result in Reduced Rat Frontal Cortex Synaptophysin Protein Levels at Adulthood as Opposed to Postmortem Findings in Schizophrenia

Abstract: Synaptophysin, a synaptic vesicle protein and a marker for synaptic density has been found to be reduced in postmortem prefrontal cortex of schizophrenia patients, consistent with evidence for synaptic deficits in schizophrenia. The contribution of both genetic and environmental factors to the etiology of schizophrenia is well established, and obstetric complications have been suggested as a non-genetic risk factor of schizophrenia. As there is only scarce evidence for a genetic linkage between synaptophysin's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…This is probably dependent on the regulation of cytoskeletal components which determine cell polarity and motility as well as neuritogenesis (Narumiya et al, 1997;Luo, 2000). They are also likely to play a role in other neuronal responses to NMDA (Harris et al, 2003;Norenberg et al, 1999) including excitotoxicity and neuronal development (Koh et al, 2006;Ahnert-Hilger et al, 2004;van Aelst and Cline, 2004) This negative result is especially interesting in view of reports that changes in the levels of synaptophysin and VAMP-1 occur in brain tissue from schizophrenic patients (Halim et al, 2003;Maycox et al, 2009;Nadri and Agam, 2009). It is possible, however, that changes may have occurred before the P21 time point at which they were first examined in this study, since Afadlal et al (2010) reported that prenatal stress induced by maternal restraint or corticosterone injections produced a decrease in synaptophysin levels only in animals at P7 or P14, but not at later ages such as the P21, post-weaning time examined here.…”
Section: Protein Expressionmentioning
confidence: 99%
“…This is probably dependent on the regulation of cytoskeletal components which determine cell polarity and motility as well as neuritogenesis (Narumiya et al, 1997;Luo, 2000). They are also likely to play a role in other neuronal responses to NMDA (Harris et al, 2003;Norenberg et al, 1999) including excitotoxicity and neuronal development (Koh et al, 2006;Ahnert-Hilger et al, 2004;van Aelst and Cline, 2004) This negative result is especially interesting in view of reports that changes in the levels of synaptophysin and VAMP-1 occur in brain tissue from schizophrenic patients (Halim et al, 2003;Maycox et al, 2009;Nadri and Agam, 2009). It is possible, however, that changes may have occurred before the P21 time point at which they were first examined in this study, since Afadlal et al (2010) reported that prenatal stress induced by maternal restraint or corticosterone injections produced a decrease in synaptophysin levels only in animals at P7 or P14, but not at later ages such as the P21, post-weaning time examined here.…”
Section: Protein Expressionmentioning
confidence: 99%
“…To the best of our knowledge, there are only limited and inconsistent data on the effect of neonatal hypoxia and/or ischemia on SYN expression in the mPFC. In a different P7 model of brain anoxia, SYN protein levels in the frontal cortex were elevated 4 weeks after exposure (Nadri & Agam, 2009). In a model of perinatal asphyxia, no alterations in synaptic plasticity in the frontal cortex were observed as assessed by the presynaptic bouton density (Van de Berg et al., 2000); however perinatal anoxia decreased dendritic spine density in PFC neurons (Juárez, Gratton, & Flores, 2008).…”
Section: Discussionmentioning
confidence: 99%